Women on the Edge in Early Modern Europe - Norrie, Aidan; Hopkins, Lisa (Book collections on Project MUSE., 2019)
Women on the Edge in Early Modern Europe examines the lives of women whose gender impeded the exercise of their personal, political, and religious agency, with an emphasis on the conflict that occurred when they crossed the edges society placed on their gender. Many of the women featured in this collection have only been afforded cursory scholarly focus, or the focus has been isolated to a specific, (in)famous event. This collection redresses this imbalance by providing comprehensive discussions of the women's lives, placing the matter that makes them known to history within the context of their entire life. Focusing on women from different backgrounds - such as Marie Meurdrac, the French chemist; Anna Trapnel, the Fifth Monarchist and prophetess; and Cecilia of Sweden, princess, margravine, countess, and regent - this collection brings together a wide range of scholars from a variety of disciplines to bring attention to these previously overlooked women